Perbedaan Berat Badan Sebelum dan Sesudah Terapi Akupuntur - Makaba, Sarce; Matturungan, Minhas; Hasmi, Hasmi; Zainuri, Agus; Tingginehe, Rosmin M.; Medyati, Novita (Journal of Telenursing (JOTING), 2024)
This study aims to determine the difference in patient weight before and after acupuncture therapy at Rajawali Clinic Jayapura. The method used is an analytical quantitative method with a survey approach. The results showed that respondents consisted of 67% women and came from non-Papuan tribes by 64%. The age of respondents is dominated by the age group of 25-64 years (96%) and education is dominated by college graduates by 78%. Respondents' jobs were dominated by civil servants at 62%. The results of the Wilcoxon test show that the value of sig. (2-tailed) of 0.000 < 0.05 which means that there is a significant difference in patient weight before and after acupuncture therapy at Rajawali Clinic Jayapura. Keywords: Acupuncture, Weight, Therapy.